Hubungan Kualitas Produk, Pelayanan Pelanggan, Desain Produk Dalam Meningkatkan Tingkat Kepercayaan Pelanggan Indosat IM3: Study Kasus Mahasiswa STIE “Koperasi Malang” - Dita Rachmawati, (JURNAL EKONOMI, KEUANGAN, PERBANKAN, KEWIRAUSAHAAN DAN KOPERASI, 2022)
In this research, the respondents who will be researched are people who are IM3 customers, especially among young people, and this study uses STIE "Koperasi Malang" students as the research population. The sample in this study is devoted to students of STIE "Koperasi Malang" because it is hoped that they already have knowledge about this research and can help provide reliable data. The data produced in this study will be utilized to tackle current issues, thus it must be genuinely dependable and accurate. The data utilized in this study was gathered using the questionnaire approach, which involves data gathering procedures such as handing out a questionnaire, a series of questions, or written comments to respondents. The results showed that the product quality variable, which was the cause of the high score, and product quality had the greatest influence, which was seen in the results of multiple linear regression analysis where the research findings and the results showed the product design variable. This variable is the variable with the second largest influence after quality. product. The results of the study show that the price variable has a high score level where this variable is the third most influential variable. And then the results showed that the service quality variable, which is a high score level where research findings on respondents' perceptions are assessed, that most respondents stated that IM3 service quality provided good service. This variable is the fourth most influential variable. The results of the study indicate that the confidence variable has a high score level where this variable is the variable with the least effect. The trust variable has a positive and significant effect on customer loyalty.